HỌC HỎI KHÁM PHÁ VÀ KẾT QUẢ LÀM VIỆC CỦA NHÂN VIÊN: NGHIÊN CỨU TRONG MÔI TRƯỜNG GIÁO DỤC ĐẠI HỌC Ở VIỆT NAM - Trần, Hà Minh Quân (Trường Đại học Đà Lạt, 2023)
This paper aims to examine the effects of exploratory learning and risk taking on individual employee performance. The research question was empirically tested in the higher education setting using 181 survey questionnaires from academics of a top public university in Vietnam. The findings confirm that exploratory learning has a positive impact on employee performance. In addition, risk taking, one of the organizational learning capability dimensions, has a moderating effect on this relationship. Specifically, the greater the risk taking, the stronger the relationship between exploratory learning and employee performance. This study discusses some implications for management in the university setting generally, and in Vietnam particularly, in enhancing their academics’ performance through exploratory learning, thereby helping them to keep up with global changes and improve their competitiveness.